2017
DOI: 10.1186/s12889-017-4518-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk of chronic liver disease in post-menopausal women due to body mass index, alcohol and their interaction: a prospective nested cohort study within the United Kingdom Collaborative Trial of Ovarian Cancer Screening (UKCTOCS)

Abstract: BackgroundWe investigated the risk of chronic liver disease (CLD) due to alcohol consumption and body mass index (BMI) and the effects of their interaction in a prospective cohort study of women recruited to the UKCTOCS trial.Methods95,126 post-menopausal women without documented CLD were stratified into 12 groups defined by combinations of BMI (normal, overweight, obese) and alcohol consumption (none, <1–15, 16–20 and ≥21 units/week), and followed for an average of 5.1 years. Hazard ratios (HR) were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
3
9
0
1
Order By: Relevance
“…Trembling et al found in a large cohort of postmenopausal women that those who were overweight or obese and drank the most alcohol had the highest risk of developing liver related events. However also abstainers had an increased risk 30. This last observation highlights the controversial issue of moderate amounts of alcohol having the potential to be protective as several studies suggest 31 32…”
Section: Epidemiologymentioning
confidence: 85%
“…Trembling et al found in a large cohort of postmenopausal women that those who were overweight or obese and drank the most alcohol had the highest risk of developing liver related events. However also abstainers had an increased risk 30. This last observation highlights the controversial issue of moderate amounts of alcohol having the potential to be protective as several studies suggest 31 32…”
Section: Epidemiologymentioning
confidence: 85%
“…We have previously evaluated potential confounding risk factors in univariate Cox proportional hazards models to determine their individual associations with liver disease, confirming that deprivation score and self-reported hypertension, heart disease, hypercholesterolaemia and diabetes were all independently associated with risk [10].…”
Section: Discussionmentioning
confidence: 72%
“…Of the 95,126 participants from UKCTOCS studied (see Trembling et al, 2018 for details of this cohort) [10], 325 participants experienced a first LRE, of which 58 had recorded risk factors and at least three serial serum samples stored. These cases were matched to 116 controls as described above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large cohort of post-menopausal women we observed more clinical events attributable to cirrhosis amongst women who were overweight or obese compared to those with a normal BMI. Although there was no evidence of significant interaction between alcohol and BMI, the highest risk of liver disease was seen in women who were overweight or obese and consumed the most alcohol [ 7 ].…”
Section: Introductionmentioning
confidence: 99%